A STUDY ON STUDENTS' DIRECT LISTENING STRATEGIES IN COMPREHENDING A PASSAGE AT THE SECOND GRADE STUDENTS OF SMAN OLAHRAGA RIAU - Kurniawan Kurniawan (Universitas Lancang Kuning, 2016)
The purpose of this research was to identify the students' direct listening strategies in comprehending a passage at the second grade students of SMAN Olahraga Riau. The design of this research was survey attitudes and practices. Sample of the research was 50 students at the second grade students of SMAN Olahraga Riau. The instrument that was used was questionnaire. The questionnaire was design the students' direct listening. The questionnaire was analyzed by using descriptive statistics and Likert scale. The result of analyzing data in terms of memory strategy, the students' mean score was 3.99 in moderate level. In terms of cognitive strategy, the students' mean score was 3.74 in moderate level, while in terms of compensation strategy, the students had mean score 3.86 in moderate level. In conclusion, the students were interested using memory strategy as the main direct strategy in comprehending a passage at the second grade students of SMAN Olahraga Riau. Keywords : Direct Listening Strategy, Comprehension, and Passage